Effects of Different Doses of Fentanyl on the Sedation of Infants Under Mechanical Ventilation; A Randomized Clinical Trial - Bita Najafian; Hamed Eyvazloo; Mohammad Hossein Khosravi (Baqiyatallah University of Medical Sciences, 2017)
Background: Respiratory distress syndrome (RDS) is a medical emergency in infants resulting from a lack of or deficiency in surfactant, and leads to pulmonary failure. Surfactant and mechanical ventilation are among the primary treatments for helping infants with respiration. Some sedative drugs, such as benzodiazepines and opioids, are used to reduce stress and restlessness in infants under mechanical ventilation. Objective: This study aimed to evaluate the effect of 2 different dosages of Fentanyl on sedation of infants under mechanical ventilation. Methods: In this randomized clinical trial, infants with RDS were assessed, and restless infants under mechanical ventilation were included in the trial. Infants were randomly allocated into 2 groups. Infants in group A underwent treatment with 0.5 μg/kg fentanyl, and those in group B received 1 μg/kg of fentanyl. Demographic information as well as data on the duration of mechanical ventilation, length of hospital stay, and need for re-intubation were recorded on a pre-designed checklist. Results: Ultimately, 60 infants (46 male and 14 female) with a mean gestational age of 36.7±1.48 weeks in group A and 36.2±1.42 weeks in group B underwent analysis (P=0.087). Patients in group A were hospitalized for 10.36±3.59 days, and those in group B were hospitalized for 10±3.95 days (P=0.642). Mean duration of mechanical ventilation was 3.96±2.02 days in group A and 3.51±1.5 days in group B infants (P=0.459). Conclusion: The findings of the present study suggest that both doses of fentanyl (0.5 μg/kg and 1 μg/kg) reduced all parameters of respiratory distress, such as heart rate and respiratory rate, with no significant difference between the 2 doses.